Enhancing the performance of Malaysian library websites: A comprehensive analysis of web load performance - Mohd Faizal Hamzah; Ranita Hisham; Khalilah Abd Hafiz; Ron Ely Julian; Zawawi Tiyunin (Association for Computing Machinery, 2025)
This paper aims to assess the load time performance of library websites in Malaysia, considering the widespread transition of libraries towards digital platforms. Ensuring the accessibility and optimal performance of library websites is paramount to meeting the evolving expectations of users. A prolonged load time negatively impacts user interest, potentially hindering access to vital library resources. The study systematically recorded and evaluated website load times on both desktop and mobile devices, utilizing an online service for web page load assessment. Additionally, the research provides insights into the accessibility percentage for each library website, acknowledging the significance of inclusive design practices. Incorporating data from 121 libraries, the findings reveal a notable discrepancy in the load times between desktop and mobile versions of library websites. The study underscores the critical importance of addressing load time disparities to enhance user experience and ensure the effectiveness of library services in the digital era. The results contribute to the broader discourse on optimizing digital library infrastructure, shedding light on practical considerations for libraries navigating the transition to digital platforms in Malaysia and beyond. This research serves as a valuable resource for library administrators, policymakers, and researchers seeking to enhance the digital accessibility and usability of library services.